Does the Strasbourg European Court protect all human rights equally? - Javier Borego Borego (Chrześcijaństwo-Świat-Polityka)
The text opens with a recollection of St John Paul II's historic visit to a mosque in 2001, highlighting the cultural respect manifested the event. The text then delves into St John Paul II's early fascination with literature and drama, emphasizing his resistance to Nazi occupation through cultural means.  The author quotes St John Paul II's statement that faith must become culture in order to be fully embraced and lived. The author urges the audience to approach Catholic culture wisely  and quotes St John Paul II's encouragement not to be afraid of the future, emphasising the capacity for wisdom and virtue in individuals. The text then moves on to a critical analysis of the European Court of Human Rights , pointing out instances of procedural irregularities and dissenting views on judgements related to issues such as abortion and the recognition of civil marriage. The author then develops his argument by utilizing the format of a play, metaphorically titled  'Abdi Ibrahim v Norway', as a case study illustrating the impact of Islam on Europe , political correctness and social unrest.